Adaptive management approach – Kansas City success story - Saša Tomić (Cambridge Prisms: Water)
The Kansas City, Missouri Smart Sewer Program has successfully implemented an adaptive management approach to cost-effectively reduce sewer overflows. This approach was implemented under the guidance of the third Consent Decree modification, which mandates the level of sewer overflow reduction. This approach includes iterative decision-making, continuous monitoring and flexible strategies to optimize environmental outcomes while managing costs. The adaptive management framework integrates system performance and past project data into an iterative planning, implementation, monitoring and analysis cycle. This process enables cost-effective decision-making aligned with Consent Decree compliance by managing the uncertainties in sewer system data and the interdependency of proposed project outcomes. The Smart Sewer Program adopted this approach in response to financial challenges and environmental requirements, resulting in key modifications to its original Overflow Control Plan projects. The adaptive management approach, enabled by the third Consent Decree modification, has proven pivotal in optimizing project performance, reducing costs and protecting vulnerable populations. By leveraging the adaptive management approach, Kansas City has reduced program expenses by hundreds of millions of dollars while aligning with Environmental Protection Agency (n.d.) environmental justice goals. Key project modification examples from the program presented in this article illustrate the effectiveness of adaptive management in achieving better outcomes. The first example showcases a project substitution. In this example, green infrastructure replaced a proposed relief sewer project, resulting in a more cost-effective solution with enhanced overflow reduction and environmental justice benefits. The second example involves project augmentation with creek separation, resolving double-counted sewer overflows, and significantly reducing annual overflow volume at minimal cost. A third example demonstrates project modification for a City project that was not a part of the Smart Sewer Program, where alternative gate configurations increased overflow capture without additional costs, potentially eliminating the need for a costly deep tunnel project. This article demonstrates the potential of an adaptive management approach for urban wastewater management programs, offering a replicable model for other municipalities. The Kansas City Smart Sewer Program example demonstrates how adaptive management can drive cost savings, enhance environmental outcomes and ensure regulatory compliance for a Consent Decree.